Determinant factors of stunting incidence in Muara Enim Regency, South Sumatra Province - Susyani, Susyani; Sartono, Sartono; Sadiq, Ahmad; Telisa, Imelda; Terati, Terati; Sari, Devy Kartika; Friantini, Tri; Hasyim, Hamzah (Intelektual Pustaka Media Utama, 2023)
Early-life chronic malnutrition causes stunting. In 2021, Muara Enim Regency had a 24.8% stunting incidence, which is still higher than the stunting prevalence in South Sumatra at 24.4%. This research aims to look into the factors contributing to stunting in the Muara Enim. The study's design was cross-sectional, with a sample of children aged 6-59 months living in the Rambang sub-district of Muara Enim Regency. There are 269 children under five were selected as samples using a stratified random sampling procedure. The chi-square test and multiple logistic regression analyses were utilized for data analysis. The findings revealed that five variables, including birth length (p=0.224 OR=1.684), exclusive breastfeeding (p=0.009 and OR=2.590), mother's height (p=0.028 OR=1.834), mother's education level (p=0.001 OR=0.488), and ownership of latrine (p=0.045 OR=0.470), had a relation with stunting incidence. According to the multiple logistic regression test result, the most influential variable associated with the stunting incidence was the mother's level of education, with OR=2.369 (95% CI OR=1.376-4.078), indicating that mothers with lower levels of education were 2.37 times more likely to have children with stunting than mothers with higher levels of education.